Four new species of Nazeris Fauvel from Wumengshan Nature Reserve, Yunnan, China (Coleoptera, Staphylinidae, Paederinae) - Yang, Yi; Hu, Jia-Yao (Zootaxa, 2025)
Four new species of Nazeris Fauvel, 1873 from Wumengshan Nature Reserve, Yunnan, China are described and illustrated: N. wumengensis, sp. nov., N. zhaotongus, sp. nov. N. guohaoi, sp. nov. and N. serratimarginatus sp. nov. An identification key to the Nazeris species in Yunnan is provided.